Are juvenile domestic pigs (Sus scrofa domestica) sensitive to the attentive states of humans?—The impact of impulsivity on choice behaviour - Nawroth, Christian; Ebersbach, Mirjam; von Borell, Eberhard (Behavioural processes, 2013)
•Pigs were free to choose between an attentive or non-attentive unfamiliar human.•In general, pigs discriminated poorly between the different human attentive states.•We differentiated two approach styles: impulsive and non-impulsive.•Subjects chose the attentive person more frequently when using a non-impulsive approach. Previous studies have shown that apes, dogs and horses seem to be able to attribute attentive states to humans. Subjects had to choose between two persons: one who was able to see the animal and one who was not. Using a similar paradigm, we tested a species that does not rely strongly on visual cues, the domestic pig (Sus scrofa domestica). Subjects could choose between two unfamiliar persons, with only one showing attention, in three different conditions (body, head away, body turned – head front). Subjects (n=16) only showed a tendency towards the attentive human in the head away condition. However, by pooling those two conditions where the position of the human head was the only salient cue, we found a significant preference for the attentive person. Moreover, two approach styles could be distinguished – an impulsive style with short response times and a non-impulsive style where response times were relatively long. With the second approach style, pigs chose the attentive person significantly more often than expected by chance level, which was not the case when subjects chose impulsively. These first results suggest that pigs are able to use head cues to discriminate between different attentive states of humans.